A comparative study of the time and cost performance of labour-only subcontractors in the construction industry in South Western Nigeria - Fagbenle O.I. , (Penerbit UKM, 2011)
The main contractors are continuously involved in a process of transforming inputs (materials, labour and capital) into outputs such as constructed facilities but they are usually accompanied by subcontractors and financial institutions among other firms. This study therefore examined the performance of labour-only subcontractors in the Nigerian construction industry. The principal objective was to find if any significant difference exists between the time and cost performance of these speciality contractors. In achieving this objective, one hundred questionnaires were distributed to each of the four categories of respondents in the Southwestern region of Nigeria. 75, 88, 56 and 42 questionnaires were respectively filled and returned by the main contractors, labour-only subcontractors, clients and consultants in the study area. Descriptive, parametric and non parametric statistical techniques were used for the analysis. Results indicated that significant difference exists between time and cost performance of labour-only subcontractors. Their mean scores were 4.30 and 3.29 respectively. The labour subcontractor performed creditably well in project delivery (time) but there is always cost overruns when compared with the initial estimates of the projects. It was also discovered that subcontractors’ time performance is sometimes at the expense of work quality as a result of the speedy execution of work at hand in order to pave way for another engagement. It is therefore suggested that project monitoring and supervision should be given a priority attention if this procurement method is to achieve its expected success.